Effect of housing system on protein and energy requirement of White Leghorn - Anitha P (Department of Poultry Science, College of Veterinary and Animal Science, 1991)
An experiment was designed to study the influence of housing system on protein and energy requirements of strain cross White Leghorn chicken (ILM-90) from one day old to seventy two weeks of age.